2020
DOI: 10.15243/jdmlm.2021.082.2673
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cover crops on soil loss control in Gede catchment of Malang Regency, Indonesia

Abstract: Cover crop is an important factor which affects soil loss. The lost of soil potential is affected by plant morphology. The aim of this study was to elaborate on the effectiveness of the type of cover crops to soil loss in the same morphology and characteristic of soil. The study was carried out by applying erosion plots. Soil loss measurements were conducted four times in each demonstration plot. Soil loss for each plot was analyzed in the laboratory. The result showed that the most erodible soil with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The combination of earlier research revealed six relevant texts for qualitative analysis. This study examined how biochar and organic materials may improve marsh area soil fertility and production (Fitriana et al, 2020(Fitriana et al, , 2021Muddarisna et al, 2021;Muddarisna, Yuniwati, Masruroh, & Oktaviansyah, 2019;Nurul et al, 2021;Yuniwati, Utomo, et al, 2020). Figure 2 displays the analysis results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of earlier research revealed six relevant texts for qualitative analysis. This study examined how biochar and organic materials may improve marsh area soil fertility and production (Fitriana et al, 2020(Fitriana et al, , 2021Muddarisna et al, 2021;Muddarisna, Yuniwati, Masruroh, & Oktaviansyah, 2019;Nurul et al, 2021;Yuniwati, Utomo, et al, 2020). Figure 2 displays the analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…Stagnation from blocked drainage is the main issue. A 50-75 cm dry stratum, preferably 100 cm, is needed for optimum root growth (Cholily et al, 2022;Muddarisna et al, 2021;Nurul et al, 2021). A drop in groundwater levels might cause caustic sulphate soils to oxidise pyrite minerals, especially in the proximal layer.…”
Section: Ppotential Of "Tidal" Swamp Land In Indonesia For Oil Palm C...mentioning
confidence: 99%
“…Soil material begins to move on the topographical position of the upper slope. Geomorphological processes found on the upper slopes as an indicator of soil material movement are the presence of soil cracks and erosion [25]. Both of these geomorphological processes can initiate the movement of soil material, so that it can initiate the movement of material.…”
Section: Landslide Databasementioning
confidence: 99%
“…Yan et al (2018) described that soil erosion in Loss Plateau, China, decreased in the order of residential area, farmland, grassland, and forest. Meanwhile, Muddarisna et al (2021) stated that the leaves and roots of vegetation are the most important part in controlling soil loss. The increasing soil erosion and sedimentation rates influenced the functionality and lifetime of reservoirs (Atulley et al, 2022;Patro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%